Amine-grafted H-MFI zeolite precursors as acidic-basic catalysts for deacetalization-Knoevenagel condensation - Zapelini, Iago William; Lorena da Silva, Laura [UNESP]; Mintova, Svetlana; Cardoso, Dilson (Elsevier, 2023)
Amorphous and semi-crystalline precursors of zeolites have a large number of silanols that can be used to anchor organic functionalities, like silane-based amines, resulting in formation of basic sites. This work describes the use of amorphous and semi-crystalline precursors of H-MFI zeolite reacting with aminopropyltrimethoxysilane (APTMS) to produce bifunctional acidic-basic catalysts for the deacetalization-Knoevenagel condensation. The effect of precursors crystallinity on the catalytic performance is explained by the formation of Brønsted acidic sites, which catalyze the deacetalization step, and on the propylamine anchoring capacity, controlled by the amount of external silanols present in the aluminosilicate. It is shown that the aluminosilicates with lower crystallinity provide a higher yield of the end product ethyl trans-α-cyanocinnamate due to the greater number of grafted propylamine groups. These results provide new insights into the preparation of acidic-basic catalysts for converting bulky molecules.